A Voxel-by-Voxel Comparison of Deformable Vector Fields Obtained by Three Deformable Image Registration Algorithms Applied to 4DCT Lung Studies - Fatyga, Mirek; Dogan, Nesrin; Weiss, Elizabeth; Sleeman, William C.; Zhang, Baoshe; Lehman, William J.; Williamson, Jeffrey F.; Wijesooriya, Krishni; Christensen, Gary E. (Frontiers in Oncology, 2015)
Background: Commonly used methods of assessing the accuracy of Deformable Image Registration (DIR) rely on image segmentation or landmark selection. These methods are very labor intensive and thus limited to relatively small number of image pairs. The direct voxel-by-voxel comparison can be automated to examine fluctuations in DIR quality on a long series of image pairs. Methods: A voxel-by-voxel comparison of three DIR algorithms applied to lung patients is presented. Registrations are compared by comparing volume histograms formed both with individual DIR maps and with a voxel-by-voxel subtraction of the two maps. When two DIR maps agree one concludes that both maps are interchangeable in treatment planning applications, though one cannot conclude that either one agrees with the ground truth. If two DIR maps significantly disagree one concludes that at least one of the maps deviates from the ground truth. We use the method to compare three DIR algorithms applied to peak inhale-peak exhale registrations of 4DFBCT data obtained from thirteen patients. Results: All three algorithms appear to be nearly equivalent when compared using DICE similarity coefficients. A comparison based on Jacobian Volume Histograms shows that all three algorithms measure changes in total volume of the lungs with reasonable accuracy, but show large differences in the variance of Jacobian distribution on all contoured structures. Analysis of voxel-by-voxel subtraction of DIR maps shows that the three algorithms differ to a degree which is sufficient to create a potential for dosimetric discrepancy during dose accumulation. Conclusions: DIR algorithms can perform well in some clinical applications, while potentially fail in others. These algorithms are best treated as potentially useful approximations of tissue deformation that need to be separately validated for every intended clinical application.